THE INFLUENCE OF CUSTOMERS’ VALUE ON SATISFACTION AND ITS IMPACT TOWARDS LOYALTY USING IPHONE BRAND SMARTPHONE IN PALU CITY - Tandigala, Ishak Sandy; P. Adam, Rosida; Sutomo, Maskuri (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2022)
This research aims to determine the influence of customers’ value on satisfaction and its impact towards loyalty using iPhone brand smartphone in Palu city. This is descriptive-causal research. The research sample is 165 consumers who use iPhone brand smartphones in Palu City selected through purposive sampling method. The research used data analysis methods carried out by looking at the assumptions of Structural Equation Modeling (SEM) as well as conformity tests and statistical tests which are all carried out with the AMOS 16.0 and SPSS 23 programs. The research results reveal that 1) Customer value has a positive and significant influence on satisfaction using an iPhone brand smartphone in Palu City., 2) Customers’ value has a positive and significant influence on Loyalty using an iPhone brand smartphone in Palu City, 3) Customers’ satisfaction has a positive and significant influence on Loyalty using an iPhone brand smartphone in Palu City, 4) Satisfaction can mediate the influence of customers’value on loyalty using iPhone brand smartphone in Palu City. Keywords: Customers Value, Customers Satisfaction, and Customers Loyalty.